2nd international conference engineering and health in compressed air work delegate information : St Catherine's College, Oxford, UK, 25-27 September 2002 (Thomas Telford, 2002)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present.Proceedings of second international conference held at St. Catherine's College, Oxford, 25-27 September 2002.